Using P–Cl inorganic ultrafine aerosol particles to prevent spontaneous combustion of low-rank coal in an underground coal mine. (July 2020) - Tang, Yibo; Hu, Shihua; Wang, Huae
Abstract: Novel aerosol particles were developed and utilised to prevent SCC in underground goafs. The ultrafine aerosol particles (UAPs) were synthesised by grinding ammonium dihydrogen phosphate, magnesium chloride, zinc borate, talcum powder, calcium stearate, sericite, bentonite, and silica to a an equivalent spherical diameter of less than 100 μm in the ratio of 144:36:8:5:5:6:4:2. Loading of 1–5% aerosol powders inhibited the activity of O-containing functional groups such as C–O in the lignite as well as retarding its exothermic behaviour. Scanning electron microscopic analysis indicated that the aerosol particles form a uniform insulating layer on the coal surface at temperatures beyond 160 °C. Fire-extinguishing experiments showed that the P–Cl aerosol particles reduced the temperature of the burning coal to less than 100 °C within 45 min and prevented its reignition. Particles of less than 10 μm in diameter around the fire source accounted for 38.7% of the total particles transported, indicating that aerosol particles had been uniformly diffused into the confined space.